PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MELALUI METODE SIMULASI DI KELAS V SD NEGERI 11MUAROKALABAN KOTA SAWAHLUNTO - MARTATI, YESSY (Universitas Negeri Padang, 2014)
AbstrakThis research was conducted due to the students’ less motivation in the learning process. In addition, those who were in grade V of SD Negeri 11 Muaro Kalaban Kota Sawahlunto got low learning achievement in Civics. The aim of this research was to describe the improvement of the students’ learning achievement by using simulation method. Based on the result of the research, it was found out that the score of the Lesson Plan in cycle I meeting I was 75%, in cycle I meeting II was 82.14% and in cycle II meeting I was 85.7% and in cycle II meeting II was 92.85% . This result indicated that the use of simulation method was effective to improve the student’ learning achievement. This coult be seen from their average score which improved from 71.48% in cycle I 84.50% in cycle II. Key Terms: Learning Achievement in Civics by using Simulation Method